THE IMPACT OF TILLAGE AND PLANTING ON THE SOIL RESOURCE-INTENSIVE TECHNOLOGY IN THE REGION OF THE LOWLAND-STEPPE TULIP ON THE FIELD YIELD, SEEDLING NUMBER AND YIELD OF AUTUMN WHEAT - J. Nishanov; X. Yusupov (American Journal Of Agriculture And Horticulture Innovations, 2024)
In multifactorial field experiments conducted in 2022-2023, the influence of different methods and depths of processing of typical rain fed serezems, mineral fertilizers on field seed germination, stem density and productivity of winter bread wheat variety “Istiklol- 6” was studied in the conditions of the flat-hill rainfed zone of Uzbekistan.